Neural Basis of Anhedonia and Amotivation in Patients with Schizophrenia: The Role of Reward System - Suk Lee, Jung; Jung, Suwon; Park, Il H.; Kim, Jae-Jin (Current Neuropharmacology, 2015)
Anhedonia, the inability to feel pleasure, and amotivation, the lack of motivation, are two prominent negative symptoms of schizophrenia, which contribute to the poor social and occupational behaviors in the patients. Recently growing evidence shows that anhedonia and amotivation are tied together, but have distinct neural correlates. It is important to note that both of these symptoms may derive from deficient functioningof the reward network. A further analysis into the neuroimaging findings of schizophrenia shows that the neural correlates overlap in the reward network including the ventral striatum, anterior cingulate cortex and orbitofrontal cortex. Other neuroimaging studies have demonstrated the involvement of the default mode network in anhedonia. The identification of aspecific deficit in hedonic and motivational capacity may help to elucidatethe mechanisms behind social functioning deficits in schizophrenia, and may also lead to more targetedtreatment of negative symptoms.
Keywords: anhedonia